Study of charge transport behavior in organic solar cells / Shahino Mah Abdullah - Shahino Mah, Abdullah (2015)

(untitled)
The energy harnessing devices like solar cells based on organic materials known as organic solar cells (OSCs) have attracted much interest in research and industrial field as they are believed to achieve promising performance for consumers needs and become very competitive in the near future. However, as compared to commercially available inorganic solar cells, the performance of OSCs, in their existing form, is relatively low and does not suit for practical use in electronic application due to poor nature of organic material. In order to face this challenge, the study of OSCs charge transport behavior by means of electrical characterization is very crucial to provide useful knowledge for the enhancement of OSCs performance. Therefore, the study of charge transport behavior in OSCs has become the main purpose in the present research work where it is done by two types of measurements; (1) current-voltage (I-V) method, and (2) electric field induced second harmonic generation (EFISHG) technique. The study of charge carrier dynamics has been carried out, individually, for materials such as vanadyl 2,9,16, 23-tetraphenoxy-29H, 31H-phthalocyanine (VOPcPhO) a phthalocyanine derivative, and poly[N-9'-heptadecanyl-2,7-carbazole-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)] (PCDTBT) a carbazole derivative, by means of I-V method and EFISHG technique, respectively. The I-V results have unveiled the fact that VOPcPhO has an ambipolar property in which the mobility of electron (8.310-5 cm2/Vs) was found comparable with the hole mobility (3.710-4 cm2/Vs) which makes it work not only as a donor, but also as an acceptor component when combined with other donor material such as poly(3-hexylthiophene-2,5-diyl) (P3HT) in the OSCs. The EFISHG measurement was performed for both selected donor materials (VOPcPhO and PCDTBT) which showed better compatibility for the study of charge carrier in PCDTBT based devices as the technique requires non-centro symmetrical material iv structure. It is found that the hole mobility of PCDTBT measured by EFISHG technique is higher (5.610-5 cm2/Vs) than the mobilities measured by I-V method (2.410-5 cm2/Vs), time-of-flight (0.910-5 cm2/Vs), OTRACE (4.110-5 cm2/Vs), and photo-CELIV (5.010-5 cm2/Vs) methods, reported in the literature. Furthermore, study of the charge transport behavior in the OSCs, based on the blend of donor (PCDTBT) and acceptor [6,6]-phenyl C71 butyric acid methyl ester (PC71BM), was carried out by EFISHG technique. The EFISHG characterization has enabled us to discover several new facts in this work, which are stated as: the individual electric fields of both PCDTBT and PC71BM could be measured in the PCDTBT:PC71BM bulk heterojunction OSCs by using selected fundamental laser wavelengths (1000 nm for PCDTBT, and 1060 nm for PC71BM), the direction of internal electric field in PCDTBT:PC71BM solar cells was reversed (from ITO-blend-Al to Al-blend-PEDOT:PSS-ITO) by introducing a PEDOT:PSS layer leading to a longer electron transit time and thus increased efficiency of OSCs. The present study has provided a deeper insight and understanding on the mechanism of charge transport behavior in OSC devices which is very useful for the improvement of both efficiency and stability of the OSCs.